2022
DOI: 10.1155/2022/9364313
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach for Uncovering the Antitumor Effects and Potential Mechanisms of the Sijunzi Decoction for the Treatment of Gastric Cancer

Abstract: Background. Sijunzi decoction (SJZD), a classic Chinese formula, has been clinically used for the treatment of gastrointestinal disorders. However, few studies have uncovered its antitumor effects and its potential mechanisms against gastric cancer (GC). Therefore, this work aimed to identify the active compounds and putative targets of the SJZD and to further explore the potential mechanisms involved in the treatment of GC. Materials and Methods. The active compounds and potential targets of the SJZD and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Numerous studies have indicated that SJZD exhibits an anti-cancer efficacy as well as a synergistic effect in preventing cancer cachexia, alleviating inflammatory response, improving malnutrition state, and enhancing QOL. 23 , 24 , 46 - 48 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that SJZD exhibits an anti-cancer efficacy as well as a synergistic effect in preventing cancer cachexia, alleviating inflammatory response, improving malnutrition state, and enhancing QOL. 23 , 24 , 46 - 48 …”
Section: Discussionmentioning
confidence: 99%
“…Among them, four herbs constitute a typical formula in China, Sijunzi decoction, which has been shown to reduce the nuclear accumulation and DNA-binding activity of β-catenin, thereby repressing cell growth and inducing apoptosis in human GC MKN74 and MKN45 cells ( Li et al, 2021 ). Network pharmacology and experimental validation suggested that Sijunzi decoction could inhibit tumor proliferation and angiogenesis by down-regulating the expression of VEGFA, iNOS, COX-2, and Bax/Bcl2 proteins in NCG-bearing mice with human gastric adenocarcinoma cell NUGC-4, regulate the PI3K/AKT pathway, and induce apoptosis ( Ding et al, 2022 ). To further explore how seven herbs improve the short-term efficacy of platinum-based chemotherapy for AGC, we will review each herb to assess the mechanistic evidence of the specific anti-tumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study reported that ginseng diol induced apoptosis in the pancreatic cancer cell lines PANC-1 and Patu8988 through the JAK2/STAT3 signaling pathway, limiting the progression of pancreatic cancer ( Fan et al, 2021 ). Ding et al observed that Sijunzi tang, with GS as one of the main components, downregulates the expression of VEGFA, iNOS, COX-2 and Bax/Bcl2, regulates the PI3K/AKT pathway, and induces apoptosis to treat gastric cancer cells NUGC-4 ( Ding et al, 2022 ). (24r)-Ginsenoside HQ (R-PHQ) and (24s)-Ginsenoside HQ (S-PHQ) are the main metabolites of (20s)-Ginsenoside Rh₂ (GRh₂) in vivo .…”
Section: Anti-tumor Mechanism Of Action Of the Active Ingredients Of ...mentioning
confidence: 99%